2022
DOI: 10.1021/acs.jafc.1c06350
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Methods for the Analysis of Milk

Abstract: The milk and dairy industries are some of the most profitable sectors in many countries. This business requires close control of product quality and continuous testing to ensure the safety of the consumers. The potential risk of contaminants or degradation products and undesirable chemicals necessitates the use of fast, reliable detection tools to make immediate production decisions. This review covers studies on the application of electrochemical methods to milk (i.e., voltammetric and amperometric) to quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 214 publications
0
11
0
1
Order By: Relevance
“…Inductively coupled plasma mass spectroscopy (ICP-MS), and synchrotron radiation X-ray spectrometry (SR-XRF) are commonly applied to analyze trace amounts of heavy metals (Iraji et al, 2012;Zhang et al, 2017). However, these detection methods are too complex for high quantities of samples requiring real-time detection; for example, professional technicians, tedious pre-processing, and expensive equipment cannot meet the requirements of rapid and convenient detection (Motshakeri et al, 2022). Electrochemical detection technology can provide on-site, dynamic, and easy detection of heavy metal ions, and has the possibility to become a promising alternative method in the detection field.…”
Section: Introductionmentioning
confidence: 99%
“…Inductively coupled plasma mass spectroscopy (ICP-MS), and synchrotron radiation X-ray spectrometry (SR-XRF) are commonly applied to analyze trace amounts of heavy metals (Iraji et al, 2012;Zhang et al, 2017). However, these detection methods are too complex for high quantities of samples requiring real-time detection; for example, professional technicians, tedious pre-processing, and expensive equipment cannot meet the requirements of rapid and convenient detection (Motshakeri et al, 2022). Electrochemical detection technology can provide on-site, dynamic, and easy detection of heavy metal ions, and has the possibility to become a promising alternative method in the detection field.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, food safety has gathered considerable attention owing to the continuous occurrence of food contamination incidents. Owing to this reason, the present work also explores the potential of PPESI-MS in determining different pesticides in fluidic samples such as milk and orange juice. After investigating the performance of PPESI-MS, it was found that the packed adsorbent type significantly impacted the analysis sensitivity.…”
Section: Resultsmentioning
confidence: 99%
“…Abaci [ 66 ] developed an electrochemical sensor modifying a pencil graphite electrode with graphene oxide (GO) to determine β-lactoglobulin (β-LB). It is well known that β-LB, the main whey protein, causes an allergic reaction in humans and it is one of the main reasons for cow milk allergies [ 64 , 67 , 68 ].…”
Section: Electrochemical Biosensors For Food Allergen Detectionmentioning
confidence: 99%